Evaluasi Penggunaan Antibiotik Pada Pasien Pneumonia Komuniti Pediatrik Di Instalasi Rawat Inap Rumah Sakit Umum Daerah Dr. Moewardi Tahun 2015 - Jayanti, Stevany Dwi, Ambar Yunita Nugraheni, M.Sc., Apt (2017)
Pneumonia is low respiratory tract infection that affects lung parenchyma, respiratory bronchioles and alveoli. Community Acquired Pneumonia(CAP) occurred from external environment, not from the hospital. According to the Basic Health Research (RISKESDAS), pneumonia is the second cause of death after diarrhea (15.5% of all children). It shows that pneumonia becomes major health problems associated with the high mortality of children under five in Indonesia. The use of antibiotics can lead to bacterial resistance, there by increasing the toxicity and side effects. The use of antibiotics ineffective, unsafe and unecomic at this time has been a service health problem. Purpose of this study was to determine the exactness of the use of antibiotics for pediatric patients that have pneumonia in Hospital of Dr. Moewardi year 2015, based on rationality of drug use, which is for the right patient, right indication, right medication and the right dosage. This type of research classified as a non-experimental research conducted retrospectively with a descriptive method. The sampling technique used is purposive sampling. The sample are pediatric patients (0-14 years of age) who are hospitalized in the Hospital of Dr. Moewardi year 2015 diagnosed with CAP and received antibiotics therapy. The data for rationality of drug use analysis including evaluation of the right patient, indication, right medication and the right dose aspects based on reference guide Medical Services Pediatric Association Indonesia in 2009 and the British National Formulary for Children 2011-2012. The results of this research of 36 pediatric patients diagnosed with CAP found that the antibiotics used are a combination of Ampisilin-Gentamisin (44,44%), Cefotaksim-Gentamisin (22,22%), Ceftriakson (11,11%), Ceftriakson-Gentamisin (8,33%), Ampisilin-Kloramfenikol (8,33%), and Ceftriakson-Kloramfenikol (5,55%). The result of evaluation that utilization of antibiotic was 100% right indication, 100% right patients, and 100% right medication, but only 2,77% are on the right dose.